Environmental Responsibility, Active Social Learning, and Political Action - Hayes, David (PRISM: Casting New Light on Learning, Theory and Practice, 2017)
Critical criminology will be applied to a discussion of environmental responsibility and the proposed controversial practice of ’fracking’. First, Green Criminology is discussed, as it seeks to re-direct the traditional focus of criminology onto patterns of crime and forms of criminality often marginalised by dominant research agendas and discourses. Green Criminology seeks to examine behaviours and actions that may not necessarily be deemed criminal, but can potentially or actually cause social and environmental harm. Links will be made throughout between environmental issues, economic development and social and environmental justice. Another key feature of Green Criminology is the way in which it seeks to align with environmental activism, and an account will be given here of ethnographic research into a contemporary environmental protest movement, the ’anti-fracking’ movement. In relation to this movement and its potentiality, there will be a particular focus on what is known as active social learning and the ways in which community views can be formalised in order to facilitate a dialogical relationship with representative structures. In the context of environmental responsibility, the case for active social learning as a critical pedagogy is the need to find ways of interacting that bring about necessary changes in situations where there is much we don’t know and need interactions with others to find out, with an emphasis on the co-creation of knowledge. This can be seen as vital for the development and success of social/environmental and political movements, as well as for creating and preserving the conditions for genuine participatory democracy.